Evaluation tool for a gastroenterostomy simulated training - Barreira,Márcio Alencar (2019)
Abstract Purpose: To create a checklist to evaluate the performance and systematize the gastroenterostomy simulated training. Methods: Experimental longitudinal study of a quantitative character. The sample consisted of twelve general surgery residents. The training was divided into 5 sessions and consisted of participation in 20 gastroenterostomys in synthetic organs. The training was accompanied by an experienced surgeon who was responsible for the feedback and the anastomoses evaluation. The anastomoses evaluated were the first, fourth, sixth, eighth and tenth. A 10 item checklist and the time to evaluate performance were used. Results: Residents showed a reduction in operative time and evolution in the surgical technique statistically significant (p<0.01). The correlation index of 0.545 and 0,295 showed a high linear correlation between time variables and Checklist. The average Checklist score went from 6.8 to 9 points. Conclusion: The proposed checklist can be used to evaluate the performance and systematization of a simulated training aimed at configuring a gastroenterostomy.